Autoimmune Thyroiditis and Glomerulopathies - Santoro, Domenico; Vadalà, Carmela; Siligato, Rossella; Buemi, Michele; Benvenga, Salvatore (Frontiers in Endocrinology, 2017)
Autoimmune thyroiditis (AIT) is generally associated with hypothyroidism. It affects approximately 2% of the female population and 0.2% of the male population. The evidence of thyroid function- and thyroid autoantibody-unrelated microproteinuria in almost half of patients with AIT and sometimes heavy proteinuria as in the nephrotic syndrome point to a link of AIT with renal disease. The most common renal diseases observed in AIT are membranous nephropathy, membranoproliferative glomerulonephritis, minimal change disease, IgA nephropathy, focal segmental glomerulosclerosis, anti-neutrophil cytoplasmic autoantibody (ANCA) vasculitis and amyloidosis. Different hypotheses have been put forward regarding the relationship between autoimmune thyroiditis and glomerulopathies, and several potential mechanisms for this association have been considered. Glomerular deposition of immunocomplexes of thyroglobulin and autoantibodies as well as the impaired immune tolerance for megalin (a thyrotropin-regulated glycoprotein expressed on thyroid cells) are the most probable mechanisms. Cross-reactivity between antigens in the setting of genetic predisposition has been considered as a potential mechanism that links the described association between ANCA vasculitis and AIT.